Mobile-assisted language learning: A Duolingo case study - Loewen, Shawn; Crowther, Dustin; Isbell, Daniel R.; Kim, Kathy Minhye; Maloney, Jeffrey; Miller, Zachary F.; Rawal, Hima (ReCALL (Cambridge, England), 2019)
The growing availability of mobile technologies has contributed to an increase in mobile-assisted language learning in which learners can autonomously study a second language (L2) anytime or anywhere (e.g. Kukulska-Hulme, Lee & Norris, 2017; Reinders & Benson, 2017). Research investigating the effectiveness of such study for L2 learning, however, has been limited, especially regarding large-scale commercial L2 learning apps, such as Duolingo. Although one commissioned research study found favorable language learning outcomes (Vesselinov & Grego, 2012), limited independent research has reported issues related to learner persistence, motivation, and program efficacy (Lord, 2015; Nielson, 2011). The current study investigates the semester-long learning experiences and results of nine participants learning Turkish on Duolingo. The participants showed improvement on L2 measures at the end of the study, and results indicate a positive, moderate correlation between the amount of time spent on Duolingo and learning gains. In terms of perceptions of their experiences, the participants generally viewed Duolingo’s flexibility and gamification aspects positively; however, variability in motivation to study and frustration with instructional materials were also expressed.